The contradictions of media power - Freedman, Des, 1962- (London ; New York : Bloomsbury, 2014)
"Media power is a crucial, although often taken for granted, concept. We assume, for example, that the media are 'powerful'; if they were not, why would there be so many controversies over the regulation, control and impact of communicative institutions and processes? Further, we assume that this 'power' is somehow problematic; audiences are often treated as highly susceptible to media influence and too much 'power' in the hands of one organization or individual is seen as risky and potentially dangerous. These concerns have been at the heart of recent controversies involving the relationships between media moguls and political elites, the consequences of phone hacking in the UK, and the emerging influence of social media as vital gatekeepers. Yet it is still not clear what we mean by media power or how effective it is. This book evaluates contrasting definitions of media power and looks at the key sites in which power is negotiated, concentrated and resisted - politically, technologically and economically. Combining an evaluation of both previous literature and new research, the book seeks to establish an understanding of media power which does justice to the complexities and contradictions of the contemporary social world. It will be important reading for undergraduates, postgraduates, researchers and activists alike"--
Includes bibliographical references (pages 147-167) and index.
Keywords: Mass media -- Political aspects; Mass media -- Social aspects; Mass media -- Influence; SOCIAL SCIENCE / Media Studies; POLITICAL SCIENCE / Political Freedom & Security / Civil Rights